SAFETY AND EFFICIENCY OF XYLEM WATER TRANSPORT IN TWO CASHEW (Anacardium occidentale L.) STRAINS AT THE SEEDLING STAGE - PITONO, JOKO; MAKOTO, TSUDA (Jurnal Penelitian Tanaman Industri, 2012)
ABSTRACTAs cashew trees are grown by transplanting seedlings, the seedlingoften suffers from drought damaged due to prolonged dry season. Previousstudy found that the ability to maintain water transport in xylem related todrought resistant character. To determine whether there was trade-offbetween the ability to maintain water transport in xylem and an efficiencyof water transport, differences in xylem vulnerability to dysfunction,hydraulic conductance, and the relationship to xylem vessel diameter wereexamined in two cashew strains. The xylem vulnerability to dysfunctionwas evaluated by the applied pressure which induced 50% loss of stemhydraulic conductivity (P 50 ). The hydraulic conductance on root, stem, andleaf were determined with High Pressure Flow Meter (HPFM). Variationsin the P 50 values were found between A3-1 and Pangkep, whereas thevalues were 1.75 and 0.50 MPa, respectively. However, since there was nodifference in the hydraulic conductance and the vessel diameter, the trade-off between the ability to maintain water transport in xylem and anefficiency of water transport did not occur in cashew. It was suggested thatgood combination of efficiency and safety of water transport enables A3-1to strongly uptake soil water either in dry or wet season resulting in goodadaptation to drought prone environment, and the P 50 value would besuitable parameter for evaluating drought tolerance of cashew at theseedling stage.Key words: cashew strain, vessel, xylem dysfunction, hydraulicconductance, droughtABSTRAKPengembangan jambu mete secara transplanting sering diikuticekaman kekeringan pada bibit akibat musim kering yang berkepanjangan.Studi awal memperlihatkan bahwa kemampuan xylem mempertahankanfungsi transportasi air merupakan karakter pertahanan penting terhadapcekaman kekeringan. Untuk mengetahui apakah terjadi kompensasi antarakemampuan pertahanan fungsi xylem dan tingkat efisiensi transportasiairnya dilakukan pengujian pada aspek kepekaan fungsi xylem, hantaranhidraulik, dan ukuran vesselnya. Kepekaan fungsi xylem ditentukan darinilai tekanan udara yang menyebabkan kehilangan 50% hydraulicconductance (P 50 ). Nilai hydraulic conductance pada akar, batang, dandaun ditentukan dengan menggunakan metode High Pressure Flow Meter(HPFM). Hasil pengujian menunjukkan terdapat perbedaan nilai P 50diantara dua strain jambu mete yang diuji, yakni secara berturut-turut 1,75dan 0,50 MPa pada strain A3-1 dan Pangkep. Karena tidak disertaiperbedaan pada hydraulic conductance dan ukuran vesselnya, makadisimpulkan tidak ditemukan nilai adanya mekanisme kompensasi antarakemampuan pertahanan fungsi xylem dan tingkat efisiensi pengangkutanair. Hal ini memungkinkan A3-1 tetap dapat menyerap air tanah secaracukup, baik pada musim kering maupun musim basah, dan mampuberadaptasi dengan baik di daerah rawan kekeringan. Dan nilai P 50 dapatdijadikan sebagai parameter representatif untuk evaluasi toleransi bibitjambu mete terhadap cekaman kekeringan.Kata kunci:Â  strain jambu mete, vessel, fungsi xylem, hydraulicconductance, cekaman kekeringan